Advances in Organic Anode Materials for Na‐/K‐Ion Rechargeable Batteries. Issue 18 (14th August 2020) - Desai, Aamod V.; Morris, Russell E.; Armstrong, A. Robert
Abstract: Electrochemical energy storage (EES) devices are gaining ever greater prominence in the quest for global energy security. With increasing applications and widening scope, rechargeable battery technology is gradually finding avenues for more abundant and sustainable systems such as Na‐ion (NIB) and K‐ion batteries (KIB). Development of suitable electrode materials lies at the core of this transition. Organic redox‐active molecules are attractive candidates as negative electrode materials owing to their low redox potentials and the fact that they can be obtained from biomass. Also, the rich structural diversity allows integration into several solid‐state polymeric materials. Research in this domain is increasingly focused on deploying molecular engineering to address specific electrochemical limitations that hamper competition with rival materials. This Minireview aims to summarize the advances in both the electrochemical properties and the materials development of organic anode materials. Abstract : Sustainable electrodes : Sodium‐ion and potassium‐ion batteries are likely to contribute significantly in the upcoming years to global energy security. Sustainable electrode materials must be developed to enable this growth. Organic molecules are at the core of this technology and materials offering low‐voltage redox are improving. This Minireview tracks the progress and remaining challenges in this domain.